Narrative of N. Byron Smith - Smith, N. Byron
Narrative by Smith describing his experiences aboard the whaler Nile of Greenport, N.Y., under the command of Capt. Conklin, and his voyage (1851 September 1-1854 March 12) to the whaling grounds in the Sea of Okhotsk in the northwest Pacific via the Azores, Cape of Good Hope, Indian Ocean, and New Zealand. Smith documents the methods of capturing whales and extracting whale oil, shipboard life, and his impressions of the people and culture of the Sandwich Islands (Hawaii) and the Marquesas. Includes description of Smith's return to New London, Conn., via Cape Horn in March 1854 after having left the Nile in Hawaii and stowing away aboard the merchant vessel, Harriet Hoxie.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Mariner of Pennsylvania.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Harriet Hoxie (Ship); Nile (Whaler); Voyages and travels; Whale oil; Whaling -- Okhotsk, Sea of; Whaling ships -- New York (State) -- Greenport; Horn, Cape (Chile) -- Description and travel; Cape of Good Hope (South Africa) -- Description and travel; Hawaii -- Description and travel; Indian Ocean -- Description and travel; Marquesas Islands (French Polynesia) -- Description and travel; New London (Conn.) -- Description and travel; New Zealand -- Description and travel; Okhotsk, Sea of -- Description and travel; Pacific Ocean -- Description and travel; Whalers (Persons)